2012
DOI: 10.1002/acp.2884
|View full text |Cite
|
Sign up to set email alerts
|

Learning from Narrated Animations with Different Support Procedures: Working Memory Capacity Matters

Abstract: The present experiment tested the effects of cueing (spotlights) and of verbal instructions in narrated animations on learning outcomes as well as potential moderator effects of working memory capacity (WMC). We found that the spotlight group dwelled longer on parts that were in the focus of the narration than a no-support group (control group). Despite higher levels of experienced difficulties, the no-support group had higher learning outcomes. More importantly, we found an aptitude-treatment interaction: Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…Equivocal findings have been reported for the contribution of signaling to learning outcomes. Some studies have found significant effects (e.g., Amadieu et al 2011;Boucheix and Guignard 2005;Jin 2013), while others have found no significant effects on learning outcomes even when the signals effectively served their attention-guiding role (e.g., de Koning et al 2010;Kriz and Hegarty 2007;Skuballa et al 2012). None of these studies reported negative effects of signaling on learning, however.…”
Section: Demonstration-based-training (Dbt)mentioning
confidence: 99%
“…Equivocal findings have been reported for the contribution of signaling to learning outcomes. Some studies have found significant effects (e.g., Amadieu et al 2011;Boucheix and Guignard 2005;Jin 2013), while others have found no significant effects on learning outcomes even when the signals effectively served their attention-guiding role (e.g., de Koning et al 2010;Kriz and Hegarty 2007;Skuballa et al 2012). None of these studies reported negative effects of signaling on learning, however.…”
Section: Demonstration-based-training (Dbt)mentioning
confidence: 99%
“…Empirical research on signaling warns that effective support for a single observational learning process (i.e., attention) does not necessarily yield greater learning (de Koning et al 2010;Kriz and Hegarty 2007;Skuballa et al 2012). In other words, this research suggests that it is desirable to obtain process measures for other activities involved in observational learning as well.…”
Section: Resultsmentioning
confidence: 89%
“…Differences in the ability to control attention and keep the information objects and goals presented to the students affect how much they may benefit from visual cues and information shown during the learning process (28) . The novelty and allure of technology-assisted learning environments stimulate students' curiosity and improve their attention levels during learning (23) .…”
Section: Discussionmentioning
confidence: 99%